Development of the monitoring and the lighting system of an electric vehicle - Atiya, Dewan Nawshin; Islam, Rafia; Sara, Ummay Honey; Choudhury, Ahmad Tausif (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.